PENDIDIKAN SPIRITUAL MENUJU PEMIMPIN DAN RAKYAT YANG BERBUDI LUHUR - I Ketut Ulianta (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2013)
Abstract To achieve a high level of advancement and prosperity, a country needs noble leader and people. Nobility is developed and nurtured by spiritual values that people learned since the earliest time in their lives. It is in the spiritual educations where the religious and highest philosophical values are embedded.Spiritual educational should not aim at achieving quantitative figures as the learning objective. Spiritual educational, instead, shoud be capable of internalizing the values in the inner self of the people. Once deeply internalized, the values will be genuinely reflected in the day to day behaviour of all people. This writing highlights some of the universal value of Hindu. All of the highest values scattered in the Hindu scripture of Weda must be spreaded over and repeatedly hum to the heart of all human being. Making these values as a living guide will give rise to noble leader and society. Keywords : Spiritual Educational, Noble leader and people